Football legends - Italia, Bob, 1955- (Bloomington, Minn. : Abdo & Daughters, 1990)
Describes the lives of sports legends Jim Brown, Joe Montana, Dick Butkus, Red Grange, Steve Largent
Keywords: Football players -- Biography; Football -- History